USM-FIG DIRECT COLLABORATES TO PROMOTE COUNTRY’S FIRST FIG INDUSTRY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 10 March 2016 – Universiti Sains Malaysia (USM) signed a Memorandum of Agreement (MoA) with Fig Direct to collaborate in the research on tissue culture for fig plants, utilising efficient and effective tissue culture technology to produce quality shoots (plantlets) from the donor plant.